Antagonism between two root-associated beneficial Pseudomonas strains does not affect plant growth promotion and induced resistance against a leaf-chewing herbivore. Issue 4 (15th March 2017) - Pangesti, Nurmi; Vandenbrande, Simon; Pineda, Ana; Dicke, Marcel; Raaijmakers, Jos M.; Van Loon, Joop J.A.
Abstract: Plant growth-promoting microbes residing on the roots may cooperate or compete, thereby affecting their collective benefit to the host plant. Pseudomonas simiae WCS417r (formerly known as P. fluorescens WCS417r) and Pseudomonas fluorescens SS101 are well known for their ability to induce systemic resistance in Arabidopsis . Here, we evaluate how these species interact on the roots of Arabidopsis thaliana Col-0 and how their co-inoculation affects plant defense to the leaf-chewing herbivore Mamestra brassicae and plant growth promotion. WCS417r and SS101, applied individually to root tips or at two different positions along the roots, established similar population densities on Arabidopsis roots. When co-inoculated at the same position on the roots, however, WCS417r established significantly higher population densities than SS101. Both upon single inoculation and co-inoculation, the two pseudomonads induced the same level of induced systemic resistance against the caterpillar M. brassicae and the same increase in plant biomass. These results suggest that combined inoculation of both Pseudomonas strains does not significantly modify the plant's defensive capacity compared to individual inoculation, resulting in a similar effect on performance of the generalist herbivore M. brassicae . Abstract : Antagonism between two root-associated beneficial Pseudomonas strains does not affect the strength of plant growth promotion and induced systemic resistance against a leaf-chewing herbivore.